Nyentana Marriage Divorce Reviewed From Balinese Customary Law And Its Consequences For Children - Ni Wayan Sridiani Diani; Dwi Ratna Kamala Sari Lukman; Ni Nyoman Ertnita Ratnadewi (IHSA Institute, 2021)
Marital divorce is a divorce in which the husband returns home. Divorce certainly has an impact on the family, especially the child, especially the status and rights of the child considering the status of the child's inheritance due to divorce of the marriage nyentana different from ordinary marriage. The method of approach is legislation and conceptual approach. The type of research is normative. The data types are primary data (marriage law) and secondary data (research results). Data collection techniques with literature studies. Qualitative methods of analysis. The result of his research that against divorce nyentana marriage reviewed from the customary law of Bali that men will return to their home with the status of mulih teruna. The custody status of the child is in the mother with the consideration that if he in certain matters does not carry out his duties as a mother then custody can be transferred to his father. In terms of inheritance the child will follow his mother's lineage